Graphene coupled with Pt cubic nanoparticles for high performance, air-stable graphene-silicon solar cells. (February 2017) - Huang, Kun; Yan, Yucong; Yu, Xuegong; Zhang, Hui; Yang, Deren
Abstract: Graphene-silicon (Gr-Si) solar cells have been intensively investigated in recent years, which exhibits a potential application of two-dimensional materials in photovoltaics. However, the pristine Gr with low carrier concentration and therefore low work function is not suitable for the fabrication of high performance solar cells. Chemical doping is an effective way to improve the carrier concentration of Gr, but it is not stable and the efficiency of solar cell suffers heavy degradation. Here, we have developed a novel Gr-Si device structure with the coupling of two-dimensional Gr with zero-dimensional Pt nanoparticles on the top of bulk Si. The utilization of Pt nanoparticle can effectively enhance the sunlight absorption of solar cells by the plasmonic effect. Meanwhile, the carrier concentration and work function of Gr get greatly improved by physical doping of high-work-function Pt nanoparticle, and therefore the potential barrier at Gr-Si interface is significantly increased. More interestingly, the photo-induced doping of Pt nanoparticles for the Gr based on charge transfer has been observed for the devices under sunlight illumination. As a result, an efficiency of 7% has been achieved for our pristine solar cells, which is much higher than that of the control ones, ~4%. These devices with integration of zero-two-three dimensional materials have excellent air-stability, much more advantageous than the chemically doped ones. The efficiency of solar cell can further reach 10% by the application of spin-coated TiO2 anti-reflective film. These results point out a new route to the fabrication of high efficiency Gr-Si solar cells for photovoltaic application. Graphical abstract: Highlights: Pt NPs coupled with Gr double the efficiency of Gr-Si solar cells. Enhancement of Pt NPs comes from their plasmonic effect and physical doping abilityon Gr. The photo-induced doping of Pt NPs on Gr is firstly reported on Gr-Si solar cells. The coupling of Pt NPs is air-stable and antireflection-coating-compatible.